PATROLOGI: SEBUAH PENGANTAR - Edison R.L. Tinambunan (Studia Philosophica et Theologica, 2002)
This article deals with “Patrology”, the theological science concerned with the writings of the Fathers of the Church. It wishes to draw some introductory elements of what we should know to delve patrology. As it is introduction, the author put forward key elements to the readers, such as knowledge of who the Fathers were, their characters, the meaning of “patrology” and “patristics”, and the importance of studying the writings of the Fathers. In spite of introduction this articles is theologically tracing some interesting things for every one who wants to know patrology.